Aghilan anak pasangan guru raih Anugerah Canselor UMPSA - Nor Salwana, Mohammad Idris (UMPSA, 2025)
GAMBANG, 8 November 2025 - “Nobody believes in you. You lost again and again and again. It’s not over until I win.”